I. Dissociation free energies of drug–receptor systems via non-equilibrium alchemical simulations: a theoretical framework. Issue 22 (19th May 2016) - Procacci, Piero
Abstract : In this contribution I critically discuss the alchemical approach for evaluating binding free energies in drug–receptor systems, placing this methodology into the broader context of non-equilibrium thermodynamics. Abstract : In this contribution I critically revise the alchemical reversible approach in the context of the statistical mechanics theory of non-covalent bonding in drug–receptor systems. I show that most of the pitfalls and entanglements for the binding free energy evaluation in computer simulations are rooted in the equilibrium assumption that is implicit in the reversible method. These critical issues can be resolved by using a non-equilibrium variant of the alchemical method in molecular dynamics simulations, relying on the production of many independent trajectories with a continuous dynamical evolution of an externally driven alchemical coordinate, completing the decoupling of the ligand in a matter of a few tens of picoseconds rather than nanoseconds. The absolute binding free energy can be recovered from the annihilation work distributions by applying an unbiased unidirectional free energy estimate, on the assumption that any observed work distribution is given by a mixture of normal distributions, whose components are identical in either direction of the non-equilibrium process, with weights regulated by the Crooks theorem. I finally show that the inherent reliability and accuracy of the unidirectional estimate of the decoupling free energies, based on the production of a few hundreds of non-equilibrium independent sub-nanosecond unrestrained alchemical annihilation processes, is a direct consequence of the funnel-like shape of the free energy surface in molecular recognition. An application of the technique to a real drug–receptor system is presented in the companion paper.